(untitled) (Fiep Bulletin - online, 2014)
The Motor Learning Process includes a number of stages and one of its main factors is the transfer of information about the task that is intended to be performed. The verbal instruction and the demonstration of the task at hand are two of the most important parameters frequently used as instruments of the teaching field of motor skill learning. Verbal instruction includes information about the main point, the specification of the task and how it is to be performed. The demonstration, in its turn, represents a form of motor skill learning, in which a movement is demonstrated (model) to the beginner, who should be able to take in important information that will aid in the organization and performance of that shown activity using their own individual motor actions. This study intends to test the influence of these activities in adult men who have no latter experience in the activity, when learning dart throwing. The sample contained 18 male individuals (marines from the military), in between the age group of 22 and 28 years, divided into three groups of 6 individuals each: Demonstration Group (GD), Verbal Instruction Group (GI), and the Demonstration and Verbal Instruction Group (GDI).The test included two phases, the Acquisition Phase and the Transfer Test. The Independent Student T-Test was used for the evaluation of the Acquisition Phase and the Transfer Test. P<0.05 was used as the level of significance. The study showed significant differences between the GI, GD and GDI groups in the Acquisition Phase, and no significant differences in the between the GD and GDI in the Acquisition Phase and in the comparison between the three groups in the Transfer Phase. The study also emphasized the importance of demonstrating the important useful aspects of the action for learning the ability, clearing up doubts about how the action should be performed.